2021
DOI: 10.11603/ijmmr.2413-6077.2020.2.11414
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric Estimation of Age From Bone Samples of Nigerians

Abstract: Background. Age estimation is crucial in creating the biological profile of unknown skeletal remains and recently there is emphasis on the need to develop population specific forensic baseline data for easy identification of these remains. Objective. The aim of this study is to estimate age from the histomorphometric features of the bones of Nigerians. Methods. Fragments of non-pathologic bone samples were collected during orthopaedic procedures. Ground sections were prepared using Modified Frost’s manual me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It has been suggested that bone tissues with more primary osteons may be mechanically stronger, as primary osteons have smaller lamellae and vascular channels [35]. Apart from sex, our previous study showed that primary osteons correlated inversely with age [36].…”
Section: Sex Predicted Group Membership Totalmentioning
confidence: 94%
“…It has been suggested that bone tissues with more primary osteons may be mechanically stronger, as primary osteons have smaller lamellae and vascular channels [35]. Apart from sex, our previous study showed that primary osteons correlated inversely with age [36].…”
Section: Sex Predicted Group Membership Totalmentioning
confidence: 94%